A bitter pill: smallholder responses to the new green revolution prescriptions in northern Ghana. Issue 6 (17th August 2020) - Vercillo, S.; Weis, T.; Luginaah, I.
ABSTRACT: Through a qualitative case study from the Northern Region of Ghana, this paper examines smallholders' perceptions of environmental change and contemporary Green Revolution prescriptions promoted by foreign donors, NGOs and the state. These prescriptions seek to commercialise and intensify production in Ghana through increasing use of chemical fertilisers, pesticides and faster-growing seed varieties. We argue that many smallholders are reluctantly adopting the inputs and techniques of the Green Revolution in response to erratic rainfall, shortened growing seasons, and drier soils with diminished fertility, as well as other structural constraints such as increasing competition for land. Farmers' responses are also influenced by social inequalities, as gender and wealth differences affect access to agro-inputs and participation in farm contracts. Female farmers are especially disadvantaged in adoption, which is serving to widen disparities. However, even those farmers who are following the Green Revolution prescriptions are not uncritical of its impacts, as they commonly described their decision to adhere to this technical package as a short-term trade-off to meet subsistence needs at the expense of worsening soil health and increasing debt.